Use of ozone as an alternative to chlorine for treatment of soft wheat flours - Chittrakorn, Sasivimon (Kansas State University, 2008)
Ozonation was studied as an alternative to chlorination for cake flour. Ozone treatment in a wooden tumbler at room temperature was conducted. Unchlorinated flour was treated with ozone at the rate of 0.06 L/min for 10 and 36 min using 5 lb of flour. Ozonation of cake flour decreased pH and increased the lightness (L value) of flour. Baking studies using a high-ratio white layer cake formulation showed that the volume of cakes significantly increased (p< 0.05) as ozonation time increased and cakes were softer than those made with chlorinated or control flours. The cell brightness and number of cells measured by image analysis (C-Cell) of cakes from ozone treated flour for 36 min exhibited similar values to those from chlorinated flour. Cakes made from flours after lipid extraction and after lipid extraction plus ozonation had low volume, indicating that lipids play a role in cake performance. Identification of volatile compounds that contribute to the odor of ozone treated flour was conducted. Volatile compounds of chlorinated, unchlorinated, defatted control, and ozonated defatted flours were analyzed using a purge and trap instrument and GC-MS. Aldehydes, alcohols, hydrocarbons and other compounds were found in unchlorinated and chlorinated flours while the volatile compounds present in ozone treated flours were mainly aldehydes and ketones. A rapid reduction in volatile compounds was detected when ozone treated flours were stored uncovered in a fume hood. Ozonation of defatted soft wheat flour produced less volatile aldehydes than ozone treated whole flour. The optimum temperature and time for ozone treatment in a metal tumbler using a response surface methodology design was studied. Time (5, 15, and 25 min) and temperature (25, 35 and 45 [degrees]C) was used with three response parameters. The optimum ozonation time was about 8 to 11 min with the temperature range between 36 and 46 [degrees]C. Ozone treatment for 5 to 25 min at room temperature showed an increase in unextractable polymeric protein, indicating a shift of protein to a higher molecular weight. Increase in Mixograph peak time, peak viscosity, and water retention capacity were observed as ozonation time increased. The ozone treatment did not affect the transition temperature and enthalpy change of the flour samples.
Keywords: ozone; wheat flour; cake; baking; Agriculture, Food Science and Technology (0359)